1989
DOI: 10.1136/ard.48.7.590
|View full text |Cite
|
Sign up to set email alerts
|

Defective fibrinolysis in Behcet's syndrome: significance and possible mechanisms.

Abstract: SUMMARY Reduced fibrinolytic activity has frequently been reported in Behqet's syndrome, but both the underlying mechanism and its relation to the development of thrombosis are unclear.The fibrinolytic activity was studied in seven patients with Behqet's syndrome and 12 patients with idiopathic oral ulceration. The patients with Behqet's disease had significantly reduced resting tissue plasminogen activator(t-PA) both by euglobulin fibrin plate lysis and enzyme linked immunosorbent assay (ELISA), but the tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Moreover, recent reports showed that Lp(a) has a direct action on endothelial function and induces the production of tissue plasminogen activator inhibitor by endothelium cells (24 is not yet understood. On the other hand, it was reported that the reduced fibrinolytic activity caused by decreased production of tissue plasminogen activator and its increased production by endothelium due to vascular damage may contribute to thrombotic events in the patients (3,6). The mean Lp(a) level (0.312 g/1) in patients with Behfefs disease was found to be similar to the cut-off point.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Moreover, recent reports showed that Lp(a) has a direct action on endothelial function and induces the production of tissue plasminogen activator inhibitor by endothelium cells (24 is not yet understood. On the other hand, it was reported that the reduced fibrinolytic activity caused by decreased production of tissue plasminogen activator and its increased production by endothelium due to vascular damage may contribute to thrombotic events in the patients (3,6). The mean Lp(a) level (0.312 g/1) in patients with Behfefs disease was found to be similar to the cut-off point.…”
Section: Discussionmentioning
confidence: 53%
“…Sixteen subjects (35.5%) among the patients with Behfet's disease had values higher than the cut-off point, and may therefore be at a much greater risk for thrombo-atherogenesis. It has been previously reported that the thrombotic tendency and the abnormal fibrinolysis is related to the disease activity (6). Also, Lp(a) is known as an acute phase protein and is significantly correlated with acute phase reactants (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, investigations on the fibrinolytic parameters yielded contradictory results in the literature. The tissue-type plasminogen activator (tPA) antigen values were reported as normal or reduced (Aitchison et al 1989;Hamton et al 1991;Haznedaroglu et al1996;Demirer et al 2000). Normal and increased tPA activity has also been found (Hamton et al 1991;Haznedaroglu et al 1996;Demirer et al 2000).…”
Section: Response: Is Mean Platelet Volume Increased In Behcet's Disementioning
confidence: 99%
“…36,37 Behçet's vasculopathy consists of (1) Superficial and deep vein thrombosis -affecting veins anywhere in the body; (2) Arterial aneurysms -due to adventitial inflammation; (3) Pulmonary vasculitis (since pulmonary arteries are in many ways similar to veins with low O 2 concentrations and low pressures).…”
Section: Effect Of Pregnancy On Bsmentioning
confidence: 99%